Distribution maps of endemic Caspian Sea mollusks in hotspot and non-hotspot areas - Matteo Lattuada; Christian Albrecht; Frank P Wesselingh; Denise Klinkenbuß; Maxim V Vinarski; Pavel Kijashko; Niels Raes; Thomas Wilke (PANGAEA, 2019)
The Caspian Sea is renowned for its endemic mollusk biodiversity. However, over the past decades, increasing anthropogenic pressures have caused decreases in abundances and even extinction of species. Both key pressures and endemic taxa are distributed spatially unevenly across the Caspian Sea, suggesting that ecologically different taxa such as gastropods and bivalves are also affected differentially. In addition, hotspot and non-hotspot areas for these taxa might differ quantitatively in pressure scores and qualitatively in key individual anthropogenic pressures. To test this working hypothesis, hotspot areas for endemic bivalve and gastropod species were identified using stacked species ranges. Cumulative and individual pressure scores were estimated for hotspot and non-hotspot areas of bivalves and gastropods. Differences in cumulative and individual pressure scores were tested for significance using non-parametric MANOVA and Wilcoxon rank sum tests, respectively. We identified various mollusk biodiversity hotspots across locations and depths, which are differentially affected both in terms of cumulative pressure scores and in the composition of the contributing individual pressures. Similarly, hotspot and non-hotspot areas for both bivalves and gastropods are differentially affected by anthropogenic pressures. By defining endemic hotspot areas and the respective anthropogenic pressures, this study provides an important baseline for mollusk-specific conservation strategies.